Incidence and Outcome of Low Birth Weight Neonates in Combined Military Hospital Chittagong (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Incidence of low birth weight (LBW) neonates is high in the developing countries. In Bangladesh LBW accounts for one of the leading causes of less than 5 years children mortality. Long term follow up is required to reduce morbidity. Objectives: To evaluate the incidence and outcome of low birth weight neonates in a hospital set up. Methods: This prospective observational study was carried out on 67 low birth weight neonates admitted in the neonatal ICU of Combined Military Hospital (CMH) Chittagong over a period of one year. All the date was recorded in a questionnaire. Study group was regularly followed up to know outcome. Results: Out of 282 total neonatal admissions 67 (23.76%) was LBW. Thirty eight (57.71%) were preterm and 29 (43.28%) were term but small for date. Male 37 (55.22%) predominated female 30 (44.77%). Thirty one (81.57%) of preterm and 21 (72.41%) of small for gestational age (SGA) neonates had normal growth & psychomotor development. Out of 9 patients 3 (7.89%) of preterm & 6 (20.68%) of SGA neonates had developmental delay in various aspects of developmental milestones which was observed in the follow up period of this study. Four (5.97%) died in this study & one preterm neonates developed retinopathy of prematurity. Conclusion: Early follow up can find out cases with developmental delay. Early intervention can reduce morbidity. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18738 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 98-104